Implementation of Criminal Law Enforcement Against Environmental Pollution in Indonesia - Hafrida, Hafrida; Rakhmawaty, Dessy; Herlambang, M. Ricky Putra (PT. Anagata Sembagi Education, 2025)
Criminal law enforcement is an important instrument in protecting and managing the environment in a sustainable manner. This study aims to analyze the application of criminal law to environmental pollution based on Law Number 32 of 2009 and identify obstacles in its implementation. The focus of the study includes the effectiveness of criminal sanctions against polluters and factors that hinder the optimization of law enforcement. The method used is empirical juridical with a qualitative approach, through interviews, observations, and document studies at the Jambi City Environmental Office. Research shows that criminal law enforcement has not been running optimally. The administrative and restorative justice approach is more dominant, but it has not been effective in having a deterrent effect. The main obstacles include weak coordination between institutions, limited resources, and low awareness of business actors on environmental document obligations. In addition, the permissive legal culture and the infrequent application of criminal sanctions also weaken law enforcement. There is a need to strengthen synergy between agencies, increase the capacity of law enforcement officials, and balance between repressive and restorative approaches. More effective criminal law enforcement is expected to improve legal compliance and provide real protection for the environment.